2020
DOI: 10.1021/acs.jmedchem.0c00696
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Fms-like Tyrosine Kinase 3 Inhibitors: An Attractive and Efficient Method for the Treatment of Acute Myeloid Leukemia

Abstract: Fms-like tyrosine kinase 3 (FLT3) is an important member of the class III receptor tyrosine kinase (RTK) family, which is involved in the proliferation of hematopoietic cells and lymphocytes. In recent years, increasing evidence have demonstrated that the activation and mutation of FLT3 is closely implicated in the occurrence and development of acute myeloid leukemia (AML). The exploration of small-molecule inhibitors targeting FLT3 has aroused wide interest of pharmaceutical chemists and is expected to bring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 149 publications
0
20
0
Order By: Relevance
“…In the last few years, many groups have demonstrated that the concurrent inhibition of FLT3 and other kinases that promote the survival of leukemia cells results in enhanced leukemia cell killing. 6,7 Several potential therapeutic examples, including cooperation with cyclin-dependent kinases (CDKs), JAK2, MEK, Mer, or Pim, have been described (Figure 1). 8−11 In our previous work, we found that compounds based on the 8,9,10,11-tetrahydro-3H-pyrazolo [4,3-a]phenanthridine scaffold are potent FLT3 inhibitors and effectively kill FLT3-driven AML cell lines and we introduced the candidate molecule 10 (HSD1169) (Figure 1), 12 whereas six-and seven-membered rings in this novel scaffold afforded potent FLT3 inhibitors, a five-membered ring analogue of 10 was less active, and a fourmembered ring or the acyclic methyl group analogues were poor inhibitors of FLT3.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, many groups have demonstrated that the concurrent inhibition of FLT3 and other kinases that promote the survival of leukemia cells results in enhanced leukemia cell killing. 6,7 Several potential therapeutic examples, including cooperation with cyclin-dependent kinases (CDKs), JAK2, MEK, Mer, or Pim, have been described (Figure 1). 8−11 In our previous work, we found that compounds based on the 8,9,10,11-tetrahydro-3H-pyrazolo [4,3-a]phenanthridine scaffold are potent FLT3 inhibitors and effectively kill FLT3-driven AML cell lines and we introduced the candidate molecule 10 (HSD1169) (Figure 1), 12 whereas six-and seven-membered rings in this novel scaffold afforded potent FLT3 inhibitors, a five-membered ring analogue of 10 was less active, and a fourmembered ring or the acyclic methyl group analogues were poor inhibitors of FLT3.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, despite the successful drug approvals, the necessity of the continual development of novel entities that inhibit FLT3 as well as other oncogenic kinases and/or targets is still relevant. In the last few years, many groups have demonstrated that the concurrent inhibition of FLT3 and other kinases that promote the survival of leukemia cells results in enhanced leukemia cell killing. , Several potential therapeutic examples, including cooperation with cyclin-dependent kinases (CDKs), JAK2, MEK, Mer, or Pim, have been described (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…Acute myeloid leukemia (AML) belongs to hematopoietic malignancies with strong invasiveness and high heterogeneity characteristics, which mainly manifests as deregulation of proliferation, obstruction of differentiation, and apoptosis of hematopoietic progenitor cells . It is estimated that the 5-year overall survival (OS) of AML patients is less than 50%. , In addition, according to the estimation of the American Cancer Society in 2021, the number of new-onset AML cases and deaths would increase to 20,240 and 11,400, respectively; meanwhile, AML accounted for a large proportion of annual deaths due to leukemias in the United States . Recently, the World Health Organization (WHO), the National Comprehensive Cancer Network (NCCN), and the European leukemiaNet (ELN) all have established the guidelines for AML classification and risk stratification. ,, Therefore, it is urgent to develop effective strategies for the treatment of AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted therapy against tumors has exhibited great promise and developed into one of the major therapeutic strategies for tumor treatment . To date, Fms-like tyrosine kinase 3 (FLT3) is among the most striking targets for AML therapy, which is coded by FLT3 gene, and belongs to the class III receptor tyrosine kinase (RTK) family, sharing high-sequence similarities with c-KIT, c-FMS, and platelet-derived growth factor receptor (PDGFR) . FLT3 regulates proliferation and differentiation of hematopoietic progenitor cells in bone marrow and plays a significant role in hematopoiesis and leukemogenesis. Mutations in the FLT3 gene are found in approximately 30% of AML patients, including the internal tandem duplication (ITD) and tyrosine kinase domain (TKD) mutations, accounting for approximately 23 and 7%, respectively .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation